OPTIMASI PEMESINAN PEMBUATAN VARIASI TUTUP KATUB SUSPENSI UDARA HONDA GL MAX 125cc DI MESIN TURNING CNC TU-2A (Studi Kasus Kondisi Optimum nt=1 dan nt=500) - Setyono, Gatot (JHP17 (Jurnal Hasil Penelitian), 2016)
Optimization is a way to get optimum machinery condition where toreached optimization condition, usually done with optimizing toward enginecutting parameter that exist. The aim of optimization is to get cheapestproduction cost and lowest production time. In air suspension valve covervariation making in Honda GL Max 125 cc in turning machine CNC TU-2Amethod that done is analytical method with chisel age criteria (T), cutting speed(v), machine time (tm) and production cost (Cp) in turning machinery processCNC TU-2A. The result of air suspension valve cover variation making inHonda GL Max 125 cc in turning machine CNC TU-2A that time required tocompleting one product is tc = 3,90 minutes. With optimum condition analysisbetween nt = 1 with nt = 500, so obtained calculation result for economiccondition nt = 1, economic production time required tme = 20,69 minutes andeconomic production cost Cp,c = Rp. 132.193,04,-/product, productiveproduction time tm,p = 17,97 minutes, productive production cost Cp,p = Rp.133.648,69,-/product. For economic condition nt = 500, economic productiontime tm,e = 12,74 minutes and economic production cost Cp,e = Rp. 2.175,94,-/product, productive production time required tm,p = 10,06 minutes, productiveproduction cost Cp,p = Rp. 3.632,42,-/product.Keywords : Optimization, cutting speed, chisel age, production time andproduction cost.